Clinical characteristics, treatment and outcome of childhood Burkitt’s lymphoma at the Uganda Cancer Institute - Orem, Jackson; Mulumba, Yusuf; Algeri, Sara; Bellocco, Rino; Mangen, Fred Wabwire; Mbidde, Edward Katongole; Weiderpass, Elisabete (Transactions of the Royal Society of Tropical Medicine and Hygiene, 2011)
Burkitt's lymphoma (BL) is a major cause of death among Ugandan children. We studied clinical characteristics and outcomes of childhood BL over time at the Uganda Cancer Institute (UCI). A total of 1217 children (766 boys, 451 girls, mean age 6.69 years) diagnosed with BL between 1985 and 2005 were included. There were no significant changes in the proportion of boys and girls diagnosed, or in mean age at diagnosis. Facial tumor (n = 945, 77.65%) and abdominal disease (n = 842, 69.19%) were the most common presentations. The proportion of children presenting with hepatic mass, malignant pleocytosis, and advanced-stage (stage C and D) BL increased during the study period (P < 0.01). A total of 1085 children out of 1206 (89.97%) received at least one cycle of chemotherapy, and 832 of 1099 (75.71%) demonstrated objective response (i.e. complete or partial remission). The most common symptoms at BL diagnosis were fever (n = 621, 51.03%), anemia (n = 593, 48.73%), and weight loss (n = 588, 48.32%). Significant increases in the proportion of children with fever, and significant changes in the proportion of children with anemia, night sweats and severe infection were observed. HIV positivity was 3.87%, but no substantial differences in the proportion of HIV-positive children were observed. Mortality was not significantly different over time: it was similar in boys and girls, higher in older children (compared with younger ones), in those with advanced-stage BL, and HIV-positive children, but lower in children with facial tumors compared with other tumor presentations, and among those who received chemotherapy.
Keywords: Burkitt's; lymphoma; Mortality; HIV; Cancer; Pediatrics; Uganda